A SEMIOTIC ANALYSIS OF ONWARD MOVIE POSTER - Budiari, Ni Kadek Diah (Udayana Journal of Social Sciences and Humanities, 2024)
The aims of this research are to identify the semiotic signs which contain in “Oward” movie poster. to describe the meaning of semiotic signs that realized in “Onward” movie poster. The method of this research is qualitative method because the data of this research are in words not in numbers. The source of this research is “Imperfect” movie poster. The researcher uses the theory of Charles Sanders Peirce’s Triadic Semiosis to analyze the semiotic signs found in this poster. The researcher also uses the concept of advertising by Gillian Dyer to find the semiotic signs in the poster, as well as the concept of color meaning by Anna Wierzbicka to interpret the meaning of the colors contained in the poster. From the analysis, The poster told the information of the movie they watch that related to the date, location, genre of the movie. Based on the analysis of semiotic signs using Peirce’s triadic semiosis, there are verbal and visual can be intepreted by the audience namely the titles, characters, colors, and piece of events in the poster.